2020
DOI: 10.1016/j.toxrep.2020.11.004
|View full text |Cite
|
Sign up to set email alerts
|

Cytokinesis-block micronucleus assay of celecoxib and celecoxib derivatives

Abstract: Highlights New derivatives of celecoxib can improve beneficial effects with better safety profile. DNA damage in form of micronuclei has not been observed after treatment with celecoxib or any derivative. Further development of celecoxib derivatives for chemoprevention may be promising.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 27 publications
0
1
0
Order By: Relevance
“…According to the authors, lysosomal enzymes may be involved in the fragmentation of micronuclear DNA after fusion of lysosomes and micronuclei, which was observed as well (Maass et al 2018 ). Autophagy of the main nucleus and the micronucleus was furthermore described in yeast as essential step of autophagy (Otto and Thumm 2020 ). Recent publications revealed that cGAS (cyclic GMP-AMP synthase), a sensor of cytosolic DNA and mediator of immune response, can interact with LC3 and degrade micronuclei by autophagy (Zhao et al 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…According to the authors, lysosomal enzymes may be involved in the fragmentation of micronuclear DNA after fusion of lysosomes and micronuclei, which was observed as well (Maass et al 2018 ). Autophagy of the main nucleus and the micronucleus was furthermore described in yeast as essential step of autophagy (Otto and Thumm 2020 ). Recent publications revealed that cGAS (cyclic GMP-AMP synthase), a sensor of cytosolic DNA and mediator of immune response, can interact with LC3 and degrade micronuclei by autophagy (Zhao et al 2021 ).…”
Section: Discussionmentioning
confidence: 99%